The employment effects of technological innovation, consumption, and participation in global value chains: Evidence from developing Asia - Donald Jay Bertulfo; Elisabetta Gentile; Gaaitzen J. de Vries (Asian Development Bank (ADB), 2019)
Global value chains (GVCs) have been a vehicle for job creation in developing Asia, but there is mounting concern that more sophisticated and cost-effective technology could displace workers through automation or reshoring of production. We use the demand-based input-output approach in Reijnders and de Vries (2018) to examine how employment responded to consumption, trade, and technological advances in 12 economies that accounted for 90% of employment in developing Asia during the period 2005-2015. Structural decomposition analysis based on the Asian Development Bank Multiregional Input-Output Tables combined with harmonized cross-country occupation data indicates that, other things being equal, technological change within GVCs was associated with a decrease in labor demand across all sectors, and an increase in the share of nonroutine cognitive occupations. We also find that increased domestic consumption expenditures of goods and services generated an increase in labor demand large enough to offset the negative employment impact of technological change. Finally, we do not find evidence of major shifts in occupational labor demand due to reshoring.
Keywords: D57; F63; J21; O14; 330; developing Asia; employment; global value chains; reshoring; task relocation; technology